Application of low frequency vibration to the turning of ultra-high molecular weight polyethylene - Jack Rooke; Richard Bonnell; Emily Pickford; Adam Brown; David Curtis (Advanced Manufacturing: Polymer & Composites Science)
Medical implant manufacturing is a growing sector and therefore requires improved manufacturing practices. In the case of total hip arthroplasty, the most challenging component to meet the ISO standard (ISO 7206-2:2011) is the acetabular liner, often made from ultra-high molecular weight polyethylene (UHMWPE). UHMWPE machining is associated with several manufacturing challenges, including swarf control. This research used low frequency vibration (LFV), an intermittent cutting process and supercritical CO2 (scCO2) to aid chip segmentation and prevent swarf nesting. Machining trials have demonstrated a significant reduction in swarf nesting relative to a traditional process (91% reduction from LFV and 98% reduction when using LFV and scCO2). The surface roughness (Ra) also had an indirect improvement from using LFV (53% reduction on the inner hemisphere), leading to all parts meeting the roughness requirement of ISO 7206-2:2011. The results have demonstrated machinability benefits for UHMWPE, reducing the operator intervention required and component scrap rates.